New electrolytic bath for electrodeposition of protective binary FeMo and ternary FeMoP films - Barbano, E. P.; Da Silva, F. S. [UNESP]; Carlos, I. A.; Vallï¿½s, E. (Elsevier, 2017)
FeMoP coatings with promising corrosion resistance properties were performed by using trisodiumnitrilotriacetate(NTA) as chelating agent for Fe(III). The versatility of the bath to obtain uniform and protecting coatings over different substrates has been tested. The mechanism of electrodeposition of FeMoP is the same than that of the FeMo one; over the different substrates tested, the Fe(III) complex reduces to Fe(II), which, after some molybdenum oxide formation, catalyses the molybdenum oxides reduction, leading to the binary FeMo or ternary FeMoP coatings. The incorporation of P in the amorphous films (which implies a reduction of the grain size in the compact and uniform deposits) with significant molybdenum percentage induces an improvement of the corrosion resistance properties. The FeMoP coatings are promising coatings for corrosion resistance, with much lower environmental impact than hard chromium or cobalt-base films.
Keywords: Amorphous coatings; Electrodeposition; Iron-molybdenum alloys; Phosphorous